LONELINESS AND LACK OF COMMUNICATION IN ABSURD PLAYS - Waham, Jihad Jaafar (Universitas Islam Sumatera Utara (UISU), 2023)
Loneliness and lack of communication are common themes in absurd drama. This paper explores the portrayal of loneliness and lack of communication in absurd drama through an analysis of selected works of Samuel Beckett, Harold Pinter, and Eugène Ionesco. The method employed in this research is a qualitative analysis of the texts, examining the characters, settings, and language used to convey the themes of loneliness and lack of communication. The findings reach that these themes are central to absurd drama, reflecting the existential condition of modernity. The conclusion proposes that the portrayal of loneliness and lack of communication in absurd drama is a critique of the modern world, highlighting the need for connection and communication in a fragmented and isolated society. Through a close examination of the characters and their interactions, the article argues that these plays offer a critique of modern society's tendency towards isolation and lack of meaningful communication. The article also explores how the techniques of absurdism, such as non-linear plot structures and exaggerated, nonsensical dialogue; this research can contribute to the portrayal of these themes in the selected works. Overall, the article demonstrates the enduring relevance of these plays in illuminating the human condition and the challenges of social interaction in a modern world.